Anticancer screening of ethanol extract from selected piperaceae family and its determination via trypan blue staining - Wan Haifa Haryani Wan Omar,; Shahrul Hisham Zainal Ariffin,; Zaidah Zainal Ariffin,; Muhd Fauzi Safian,; Sahidan Senafi,; Rohaya Megat Abdul Wahab, (Universiti Kebangsaan Malaysia, 2010)
The Piperaceae family comprises about 1000 to 2000 of the species that are widely distributed in tropical and subtropical area. In this study, the ethanol extracts were used to evaluate the cytotoxic activity on human hepatocellular carcinoma (HepG2) and non-malignant Chang’s liver cell lines by using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. Ethanol extracts from eight Piperaceae families were selected randomly. Results showed that all eight spesies (P. sarmentosum, P. ramifilum, P. paucistigmum, P. betle, P. macronatum, P. ridleyi, P. magnibaccum and P. miniatum) showed cytotoxicity activity with Piper sarmentosum exhibit higher cytotoxicity activity with the IC50 value at 12.5 μg/mL. On the other hand, there were no cytotoxicity activity of Chang’s cell that could be induced by the ethanol extracts because the IC50 values for non-malignant Chang’s cell were greater than 30 μg/mL. Viability analysis using trypan blue showed that P. sarmentosum ethanol extract produced significant (p<0.05) decreased of HepG2 cells as compared to control (p<0.05). In conclusion, all ethanol extracts selected randomly from Piperaceae family showed cytotoxic using MTT assay. Viability analysis using trypan blue staining demonstrates that this type of analysis can become an alternative approach in determining cytotoxicity activity of cells in the presence of extracts.